Review paperCervical spondylosis: a literature review with attention to the African population - Belachew, Degefe A.; Schaller, Bernhard J.; Guta, Zenebe (Archives of Medical Science, 2007)
Cervical spondylosis, a degenerative disease of the cervical spine, intervertebral discs, ligaments and cartilaginous material, is commonly seen in individuals after the age of 40 years and is believed to be part of the normal aging process of the vertebral column. It is seen in up to 19% of asymptomatic individuals. The major clinical presentations of cervical spondylosis can be subdivided into: (i) cervical spondylotic myelopathy, (ii) cervical radiculopathy, and (iii) neck pain syndromes. There are only a few studies showing that the disease is similarly present in Africa compared to North America or Europe and that the African lifestyle may predispose to early clinical manifestations. Medline and Embase databases were searched for trials, case series or case reports published between 1966 and March 2007 with the objective of updating current knowledge about cervical spondylosis with special reference to the population in Africa. Cervical spondylosis is one of the most common causes of cervical radiculopathy, myelopathy and chronic neck pain syndromes. A lot of studies have been conducted with regard to the pathophysiology, risk factors and treatment of the disease since the early 1990s. In Africa, there exist only a few studies on this topic indicating that there are some risk factors which are somewhat different from the developed nations and which may lead to early clinical manifestation. These factors embrace mainly load carrying and fluorosis, which are prevalent in the Rift Valley areas of Africa.